Combined NSM steel bars and externally bonded GFRP in strengthening T beams - Traplsi, Abdelbaset Mahmoud (Kansas State University, 2012)
Nowadays, using the technology of FRP strengthening has become acknowledged by engineers and has reached a full acceptance. However, researchers are always looking for improvement in performance. In this study, external bonding of GFRP and near surface mounting of regular steel bars are combined to improve the behavior, delay the failure and enhance the economy of the strengthening. E-Glass FRP is selected due to its inexpensive cost and non-conductive properties to shield the NSM steel bars from corrosion. On the other hand, the use of NSM bars gives redundancy against vandalism and environmental deterioration of GFRP. An experimental program was conducted in which four full scale T beams were designed and built. All four specimens were fabricated with Grade 70 steel reinforcement and 8000 psi concrete. Only one beam was loaded beyond first cracking then exposed to highly concentrated deicing salt water to accelerate the corrosion process. All beams were tested by monotonic loading until failure. The load rate was 1 kips/min. The first specimen is tested as a control beam failing at about 15 kips. The second specimen is strengthened using two #5 steel NSM bars and 1 layer of GFRP, both extending to the support. This beam failed at 38.4 kips by GFRP debonding. The third specimen is strengthened with the same system used for the second beam. However, the NSM steel bars were cut short covering only 30% of the shear-span while the GFRP was extended to the support. This beam failed at 25.9 kips by GFRP debonding and NSM delamination due to the lack of sufficient development of the NSM steel bars and the shear stress concentration at the steel bar cut off point. Nevertheless, the fourth beam is strengthened with the same system used for the third beam. The fourth specimen was exposed to severe attack of deicing salt by immersing it in concentrated deicing salt solution for three continuous months. In order to accelerate the corrosion process, the beam was loaded beyond its cracking load before the corrosion procedure. After the completion of the three months, the beam was tested monotonically to failure. It failed at 23.2 kips indicating that some deterioration might have taken place. The failure mode was by GFRP debonding and NSM delamination like the case of Beam 3.However, it was observed after failure that the NSM bars were very well protected by the surrounding epoxy.
Keywords: NSM; Steel; Bars; Externally; GFRP; T Beams; Civil Engineering (0543)